Upland rice intercropped with forage grasses in an integrated crop-livestock system: Optimizing nitrogen management and food production - Crusciol, Carlos A. C. [UNESP]; Momesso, Letusa [UNESP]; Portugal, Jose R. [UNESP]; Costa, Claudio H. M.; Bossolani, Joao W. [UNESP]; Costa, Nidia R. [UNESP]; Pariz, Cristiano M. [UNESP]; Castilhos, Andre M. [UNESP]; Rodrigues, Vitor A. [UNESP]; Costa, Ciniro [UNESP]; Franzluebbers, Alan J.; Cantarella, Heitor (Elsevier B.V., 2021)
Intercropping upland rice with forage grasses is a potential strategy for enhancing the sustainability of agriculture in the tropical region by increasing food production, land use per unit area, nitrogen (N) cycling, and profitability. However, little is known about the appropriate N management and N use efficiency of upland rice in these complex systems. Thus, our aim was to verify the feasibility of intercropping upland rice with tropical forage grasses combined with different N management applications at sowing and sidedressing. A field experiment was carried out in three growing seasons with three intercropping systems (monocropped upland rice, upland rice intercropped with palisade grass, and upland rice intercropped with guinea grass) combined with six N applications to upland rice [0-0 (control), 100-0, 80-20, 50-50, 20-80, and 0-100 kg N ha(-1) at sowingsidedressing]. Dry matter (DM) and accumulated N were measured in upland rice and forage grasses. In addition, components of rice yield production, industrial yield, production cost, land equivalent ratio, relative N yield, relative crowding coefficient, aggressivity of upland rice with forage grasses, forage crude protein (CP) concentration, estimated animal stocking rate, and estimated meat production were determined. Despite competition between rice and forage grasses, intercropping systems had superior benefits in terms of production and land use per unit area, N cycling, and profitability compared with monoculture. Forage DM production, CP, estimated animal stocking rate, and estimated meat production increased when N fertilizer was applied at sidedressing to rice (20-80, 50-50 and 0-100 kg N ha(-1)). Rice intercropped with guinea grass produced a greater amount of biomass, indicating that this forage species may be more advantageous in tropical regions. Net profit, total aboveground biomass, total N content, land equivalent ratio, and relative N yield were greater in intercropping systems fertilized with N.
Keywords: Oryza sativa L.; Brachiaria spp.; Megathyrsus maximus; Intercropping crops; Sustainable agroecosystem